2014
DOI: 10.1063/1.4891719
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and extrinsic effects on the electrostatic field at the surface of Bi2Se3

Abstract: The time evolution of electrostatic fields near a Bi2Se3 surface after a mechanical cleave was observed using Second Harmonic Generation. By comparing samples with different bulk doping levels and samples cleaved in different gas environments, these observations indicate multiple contributions to electric field evolution. These include the intrinsic process of Se vacancy diffusion as well as extrinsic processes due to both reactive and nonreactive surface adsorbates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…We modify the Bi 2 Se 3 surface by cleaving, which is known to trigger transport processes on a time scale of 100 min. 6,10 Extensive studies on such Bi 2 Se 3 aging effects 20,21,41,42 revealed two mechanisms (see schematic of Fig. 2b): (1) formation of an electric-dipole layer due to charge transfer from adsorbates 21,42 or surface lattice relaxation 19 and (2) migration of bulk defects, mainly Se vacancies, toward the surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We modify the Bi 2 Se 3 surface by cleaving, which is known to trigger transport processes on a time scale of 100 min. 6,10 Extensive studies on such Bi 2 Se 3 aging effects 20,21,41,42 revealed two mechanisms (see schematic of Fig. 2b): (1) formation of an electric-dipole layer due to charge transfer from adsorbates 21,42 or surface lattice relaxation 19 and (2) migration of bulk defects, mainly Se vacancies, toward the surface.…”
Section: Resultsmentioning
confidence: 99%
“…2b): (1) formation of an electric-dipole layer due to charge transfer from adsorbates 21,42 or surface lattice relaxation 19 and (2) migration of bulk defects, mainly Se vacancies, toward the surface. 21,41 While the surface dipole layer is very localized (thickness of ∼ 3 nm), 21 the redistribution of bulk Se vacancies induces a more extended space-charge region (thickness of tens of nanometers). 21,41 We now relate these processes to the amplitude evolution of J yz and J x following sample cleaving (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1(c)], however, a non-negligible bulk contribution can arise from electric-field induced nonlinear susceptibility in the SCR. 11,12,16,17 The SCR is formed by accumulation of Se vacancies upon exposed to air. 12,[15][16][17] Because the interface between Bi 2 Se 3 and BaF 2 has only little amount of vacancies or defects, 22 we neglect the SCR effect near that interface.…”
Section: For Transmitted Sh Beam (2 ) Generated By a Polarization Shementioning
confidence: 99%
“…10 In the presence of a DC field, however, the field-induced second-order nonlinearity in the bulk can be significant. 11,12 This is often the case if a space charge region (SCR) exists in the bulk, for example, near the interface of a semiconductor due to band bending. For the topological insulator, Bi 2 Se 3 , near the air/Bi 2 Se 3 interface, Se vacancies tend to migrate from the bulk and accumulate at the interface; the resulting excessive amount of positive surface charges leads to the formation of SCR.…”
Section: Introductionmentioning
confidence: 99%
“…Second generation topological insulator (TI) materials such as Bi 2 Te 3 , Bi 2 Se 3 and Sb 2 Te 3 with common structural characteristics of gapped insulating bulks and metallic conducting surfaces have gained great attention in recent years 1 2 3 4 5 . TI surfaces exhibit the linear Dirac spectrum dispersion, resulting in a unique electronic property 6 ; however, optical properties and applications require further exploration. Since Bernard et al initially identified Bi 2 Te 3 as an effective saturable absorber in 2012 7 ; the application values of TIs in nonlinear photonics have received enhanced research interests.…”
mentioning
confidence: 99%